HUMAN LITERACY IN TANTRI: PEREMPUAN YANG BERCERITA AS A CHARACTER EDUCATION MEDIA - Ni Nyoman Ayu Suciartini; I Nyoman Subrata (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Balinese society considers ancestral narratives as an inevitability. Ancestral narratives, adapted into various forms such as traditions, rituals, songs, performances, dances, and even classical or modern literary works, always hold a place of significance and attention among the people. One of the well-known traditional ancestral narratives is the story of Tantri. This Tantri narrative has inspired artists, writers, and cultural scholars to present more modern works. One of them is the literary work titled